Infinitives in Child Language - Jelaska, Zrinka (Array, 2003)
When analysing a verb system or sentenc patterns, it is not easy to categorise infinitives as they are - non-finite verb forms. Thew may be viewed as objects taken by some intransitive verbs, e.g. We agreed to stay or as verbal clause, result of predicate transformation, e.g. The best thing would be for us to leave straight away. Hence, the status of the infinitive represent a complex theoretical issues comprising syntactic, semantic as well as psycholinguistic aspects. When one analyses verbs in child language there is no easy way of dividing simple sentences with infinitive objects and complex sentences involving two different clauses. This paper will deal with infinitives in different types of sentences in Croatian and English adult languages, with examples of child language. The child language data will be taken from Croatian children age 3 and 4.